Improved early warning of compact binary mergers using higher modes of gravitational radiation: a population study. Issue 2 (19th January 2021) - Singh, Mukesh Kumar; Kapadia, Shasvath J; Shaikh, Md Arif; Chatterjee, Deep; Ajith, Parameswaran
ABSTRACT: A gravitational wave early warning of a compact binary coalescence event, with a sufficiently tight localization skymap, would allow telescopes to point in the direction of the potential electromagnetic counterpart before its onset. Use of higher modes of gravitational radiation, in addition to the dominant mode typically used in templated real-time searches, was recently shown to produce significant improvements in early-warning times and skyarea localizations for a range of asymmetric mass binaries. We perform a large-scale study to assess the benefits of this method for a population of compact binary merger observations. In particular, we inject 100 000 such signals in Gaussian noise, with component masses m_1 [1, 60 ] M_ and m_2 [1, 3 ] M_ . We consider three scenarios involving ground-based detectors: the fifth (O5) observing run of the Advanced LIGO-Virgo-KAGRA network, its projected Voyager upgrade, as well as a proposed third-generation (3G) network. We find that for fixed early-warning times of 20–60 s, the inclusion of the higher modes can provide localization improvements of a factor of ≳2 for up to 60 per cent (70 per cent ) of the neutron star–black hole (NSBH) systems in the O5 (Voyager) scenario. Considering only those NSBH systems that can produce potential electromagnetic counterparts, such improvements in the localization can be expected for 5\!-\!35 per cent (20\!-\!50 per cent) binaries in O5 (Voyager). For the 3G scenario, a significant fraction of the events have time gains of a minute to several minutes, assuming fiducial target localization areas of 100–1000 deg 2 .